CdS/VS2 Heterostructured Nanoparticles as Efficient Visible‐Light‐Driven Photocatalysts for Boosting Hydrogen Evolution. Issue 8 (17th June 2022) - Niu, Mengfan; Cao, Liyun; Feng, Liangliang; He, Danyang; Li, Xiaoyi; Chen, Qian; Fu, Changle; Huang, Jianfeng
Abstract: The development of highly active, cost‐effective hydrogen‐evolving photocatalysts is of great significance to alleviate the escalating environmental pollution and depleting fossil fuel sources. Herein, a novel CdS/VS2 heterostructured nanoparticle is successfully synthesized for the photocatalytic hydrogen evolution reaction (HER) under visible‐light irradiation via a facile hydrothermal route. Experimental results demonstrate that VS2 can facilitate the absorption of visible light, enhance the electron transfer rate, as well as inhibit the recombination of photogenerated electron‐hole pairs on CdS photocatalyst. Moreover, the optimal CdS/VS2 (0.2 wt.%) hybrid exhibits prominent photocatalytic HER activity 16 times higher than the pristine CdS counterpart, even outperforming the 1 wt.% platinum‐loaded CdS. This work injects new impetus to explore efficient noble‐metal‐free cocatalysts of CdS photocatalyst for high‐efficiency photocatalytic H2 evolution. Abstract : Vanadium disulfide (VS2 ) as a noble‐metal‐free cocatalyst displays high‐activity photocatalytic H2 evolution when integrated with CdS nanoparticles under visible‐light irradiation, achieving up to 16 times higher activity than pristine CdS.